LGBTQIA+ inclusion in the global health policy agenda: A critical discourse analysis of the Lancet Commission report archive. - William E Rosa; Sofia Weiss Goitiandia; Debbie Braybrook; Nicholas Metheny; Kailey E Roberts; Meghan McDarby; Mia Behrens; Cathy Berkman; Gary L Stein; Adebola Adedimeji; Donna Wakefield; Richard Harding; et al. (PLoS ONE)
Context LGBTQIA+ people worldwide experience discrimination, violence, and stigma that lead to poor health outcomes. Policy plays a crucial role in ensuring health equity and safety for LGBTQIA+ communities. Given Lancet Commissions' substantial impact on health policy across domains, we aimed to determine how LGBTQIA+ communities and their care needs are incorporated throughout Lancet Commission reports and recommendations. Methods Using critical discourse analysis, we analyzed 102 Commissions for inclusion of and reference to LGBTQIA+ communities using 36 key terms. Three levels of analysis were conducted: 1) micro-level (overview of terminology use); 2) meso-level (visibility and placement of LGBTQIA+ references); and 3) macro-level (outlining characterizations and framing of references with consideration of broader social discourses). Findings 36 of 102 (35%) Commissions referenced LGBTQIA+ communities with 801 mentions in total. There were minimal (9/36) references made in the "Executive Summary," "Recommendations," and/or "Key Messages" sections of reports. LGBTQIA+ communities were most frequently discussed in reports related to HIV/AIDS and sexual and reproductive health. Few Commissions related to public health, or chronic conditions (9/60) referenced LGBTQIA+ communities. Some reports made non-specific or unexplained references; many discussed the LGBTQIA+ population without specific reference to sub-groups. LGBTQIA+ communities were often listed alongside other marginalized groups without rationale or a description of shared needs or experiences. We identified framings (legal, vulnerability, risk) and characterizations (as victims, as blameworthy, as a problem) of LGBTQIA+ communities that contribute to problematizing discourse. Conclusions LGBTQIA+ people were rarely included in the Commissions, resulting in an inadvertent marginalization of their health needs. Policy initiatives must consider LGBTQIA+ groups from a strengths-based rather than problematizing perspective, integrating evidence-based approaches alongside community-based stakeholder engagement to mitigate inequities and promote inclusive care and policymaking.